Divergent Cryptosporidium species and host-adapted Cryptosporidium canis subtypes in farmed minks, raccoon dogs and foxes in Shandong, China - Wang, Weijian; Wei, Yanting; Cao, Shuhui; Wu, Wenjie; Zhao, Wentao; Guo, Yaqiong; Xiao, Lihua; Feng, Yaoyu; Li, Na (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptosporidium spp. are common parasitic pathogens causing diarrhea in humans and various animals. Fur animals are widely farmed in Shandong Province, China, but the prevalence and genetic identity of Cryptosporidium spp. in them are unclear. In this study, 1,211 fecal samples were collected from 602 minks, 310 raccoon dogs and 299 foxes on two farms in Shandong and analyzed for Cryptosporidium spp. by nested PCR and sequence analyses of the small subunit rRNA gene. The overall infection rate of Cryptosporidium spp. was 31.5% (381/1,211), with a higher infection rate in raccoon dogs (37.7%, 117/310) than in foxes (32.4%, 97/299) and minks (27.7%, 167/602). By age, the highest infection rates of Cryptosporidium spp. were observed in raccoon dogs of 1-2 months, minks of 5-6 months, and foxes of > 12 months. Three Cryptosporidium species and genotypes were detected, including C. canis (n = 279), C. meleagridis (n = 65) and Cryptosporidium mink genotype (n = 37). Among the three major host species, raccoon dogs were infected with C. canis only (n = 117), while foxes were infected with both C. canis (n = 32) and C. meleagridis (n = 65), and minks with C. canis (n = 130) and Cryptosporidium mink genotype (n = 37). Subtyping of C. canis by sequence analysis of the 60 kDa glycoprotein gene identified eight subtypes. They belonged to two known subtype families, XXa and XXd, and two novel subtype families XXf and XXg, with host adaptation at the subtype family level. Notably, C. canis from foxes was genetically distant from those in other hosts. Further subtyping analysis identified three subtypes (IIIeA21G2R1, IIIeA19G2R1 and IIIeA17G2R1) of C. meleagridis and two novel subtype families Xf and Xg of the Cryptosporidium mink genotype. The presence of zoonotic C. canis subtypes in raccoon dogs and C. meleagridis subtypes in foxes suggests that these fur animals might be potential reservoirs for human-pathogenic Cryptosporidium spp.